Pemetaan Media Inovatif Layanan Bimbingan dan Konseling Secara Online - Triyanto, Agus; Dewanti, Septinda Rima; Sari, Widya Juwita (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
Online learning is facing an obstacle caused mainly by a lack of students learning interests. The situation is worsening caused by only a few creative learning media in online education. The study aims to map the kinds of innovative media in guidance and counseling delivery. The research used mix method. The research activities are surveys and in-depth interviews. The number of the subject was ninety-four school counselors in senior high school. The result of the study is a map that shows the classification of media based on its characteristics. The study also describes the constraints faced by the teacher in school while developing and applying innovative learning media. The limitations are mainly caused by the availability of computer and internet connections in schools. Another constraint is that many school counselors cannot use technology to develop interactive guidance and counseling media. The recommendation from this study is to equip the school's counselors with computers and other tools and build their skills to use technology effectively.